Studi Performa dan Analisis Kerusakan Sistem Hidrolik Excavator Mini Excavator Zhugimada - Muhammad Hisyam Ar-Rizqi; Braam Delfian Prihadianto; Sugiyanto Sugiyanto; Nyayu Aisyah (Universitas Muhammadiyah Metro, 2025)
The hydraulic system plays a vital role in supporting excavator performance by transmitting power through pressurized fluid to actuate the boom, arm, and bucket. However, fluid leakage can significantly reduce operational efficiency and performance. This study aims to analyze the hydraulic system performance of the Zhugimada mini excavator trainer unit before and after repair. Tests were conducted on three main parameters: silinder drift, silinder speed, and silinder pressure, under three load conditions zero capacity, struck capacity, and heaped capacity. The results show that leakage was caused by damage to the fittings on the arm and bucket silinders, the seal on the boom silinder, the valve connecting the tank and pump, and an electric motor speed exceeding the standard (1,491 rpm). The leakage impact was indicated by a decrease in silinder speed 1.41% for the boom, 1.34% for the arm, and 0.51% for the bucket and a 16.28% pressure drop in the boom under no-load conditions. After the repair, system performance improved significantly, with boom speed increasing by 0.92%–2.04% and arm speed by 0.82%–1.77%. The repair effectively addressed both internal and external leakage and improved the overall efficiency of the hydraulic system.